2008
DOI: 10.1002/cbdv.200890021
|View full text |Cite
|
Sign up to set email alerts
|

Pregnane Glycosides from Caralluma adscendens var. fimbriata

Abstract: Eleven novel pregnane glycosides, 2-7 and 9-13, of which four, i.e., 10-13, comprised a new pregnane-type genin exhibiting a hydroxymethylene instead of a Me group at C(19), and the known pregnane glycoside stalagmoside V (8) were isolated from whole plants of Caralluma adscendens var. fimbriata, a native Indian succulent plant. Their structures were elucidated by extensive 2D-NMR spectroscopic studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 12 publications
1
7
0
2
Order By: Relevance
“…3,6 Caralluma fimbriata is an edible succulent cactus and wild medicinal plant in the family Apocynaceae, growing in dry places, used by tribal Indians to suppress hunger and known as "famine food" with no history of adverse effects, which contains pregnane glycosides. 7 This plant has been investigated for its myriad biological effects such as antihyperglycaemic and hypolipidaemic, hepatoprotective, antioxidant activity and came out with promising results. [8][9][10] In light of above reports, it is reasonable to assume that this plant could have anticancer potential.…”
Section: Introductionmentioning
confidence: 99%
“…3,6 Caralluma fimbriata is an edible succulent cactus and wild medicinal plant in the family Apocynaceae, growing in dry places, used by tribal Indians to suppress hunger and known as "famine food" with no history of adverse effects, which contains pregnane glycosides. 7 This plant has been investigated for its myriad biological effects such as antihyperglycaemic and hypolipidaemic, hepatoprotective, antioxidant activity and came out with promising results. [8][9][10] In light of above reports, it is reasonable to assume that this plant could have anticancer potential.…”
Section: Introductionmentioning
confidence: 99%
“…It is proposed that the active components within the hydroethanolic extract of Caralluma are the pregnane glycosides, which reportedly have selective serotonin reuptake inhibitor (SSRI)-like activity. [ 29 ] One proposed notion for the mechanism of hyperphagia in PWS, is namely, that reduced serotonin (5-hydroxytryptamine; 5-HT)-mediated signaling may cause decreased signaling of satiety in the brain. [ 10 19 ] Limited studies on SSRIs in PWS[ 30 31 ] have shown some clinical efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Plusieurs especes appartenant au genre Caralluma (c. ascendens, C. dalzielli, C. penicillata, C. retrospiciens, C. russeliana, C. tuberculata), renferment des glycosides de pregnane sous forme d'esters [7][8][9][10][11][12][13][14][15]. La cytotoxicite de certains glycosides de pregnane sur differentes lignees cellulaires a ete mise en evidence [15].…”
Section: Parties Et Principes Toxiquesunclassified